Social Return on Education in 35 Cities/Districts of Central Java Province - Rr Retno Sugiharti; Gentur Jalunggono; Muhammad Farid Alfarisy (EKO-REGIONAL, 2019)
Education has a close relation to the quality of labor. With a good level of education, labor productivity will certainly increase. In addition to reducing poverty, productivity will increase economic growth. But in Jawa Tengah Province the correlation of education with economic growth shows contradictions. In Jawa Tengah, economic growth has increased quite well but the average years of schooling is elementary school graduates. By using Mincer Wage Equation, this paper Is trying to calculate social return on education within macroeconomic growth regression methods. Thispaper aims to capture relationship between education attainment and economic growth in macroeconomic ways.